Case Report: A Novel Heterozygous Mutation of CD2AP in a Chinese Family With Proteinuria Leads to Focal Segmental Glomerulosclerosis - Liu, Yu-Xing; Zhang, Ai-Qian; Luo, Fang-Mei; Sheng, Yue; Wang, Chen-Yu; Dong, Yi; Fan, Liangliang; Liu, Lv (Frontiers in Pediatrics, 2021)
Idiopathic focal segmental glomerulosclerosis (FSGS) is a relatively frequent kidney disorder that is clinically characterized by proteinuria and progressive renal failure. Genetic factors play important roles in the etiology of the disease. CD2-associated protein (CD2AP) is a crucial protein for the slit-diaphragm assembly and function. Mutations of CD2AP can contribute to FSGS development. Here, we investigate a Chinese family of four generations with unexplained proteinuria. The proband, a 12-year-old boy, was diagnosed as FSGS. Employing whole-exome sequencing (WES) and bioinformatics strategies were employed to explore the pathogenic mutation of this family. A heterozygous mutation of CD2AP gene was identified. An unknown frameshift insertion mutation (p.K579Efs*7) was identified that leads to a truncation of CD2AP protein. Bioinformatics strategies predicted that the novel mutation was pathogenic. The mutation was absent in our 200 healthy controls and located in an evolutionarily conserved site of CD2AP protein. In conclusion, we employed WES to detect the genetic lesion of FSGS patients and identified a novel likely pathogenic mutation in CD2AP gene. Our study not only expands the spectrum of CD2AP mutations but also offers genetic testing information to additional FSGS patients.